Professional military instructor identity in the South African National Defence Force - Wagner, William John; van Putten, Sonja; Rauscher, Willem (Scientia Militaria - South African Journal of Military Studies, 2021)
In 2015, the chief of human resources at the South African National Defence Force (SANDF) ordered the improvement of the instructional quality and military ethos of military instructors. This article, based on a comprehensive study in this regard, reports on the perceptions of a sample of military instructors in the SANDF on the existence of a construct, known as the professional military instructor identity and its effect on military ethos and instructional quality. A qualitative approach was followed, using an interpretivist/constructivist paradigm, involving data collection by means of a focus group discussion and expert interviews and using thematic networks analysis as data analysis method. A conceptual framework for the professional military instructor identity, consisting of sub-identities, influencing factors and identifying indicators, was constructed. Findings suggest that the professional military instructor identity is not recognised as a construct in the SANDF; however, the elements are known, although only vaguely. The findings also support the view that this situation may have affected the current declining military ethos and instructional quality of military instructors. It is concluded that the institutionalisation and popularisation of the professional military instructor identity, as well as professional recognition of military instructors in the SANDF, could improve the current situation.